PERAN NET PROFIT MARGIN (NPM) DAN PRICE TO BOOK VALUE (PBV) TERHADAP PERGERAKAN HARGA SAHAM PT HANJAYA MANDALA SAMPOERNA TBK TAHUN 2013–2024 - Yunita Kartika (Al-Ihtiram: Multidisciplinary Journal of Counseling and Social Research, 2026)
This study aims to examine the effects of Net Profit Margin (NPM) and Price-to-Book Value (PBV) on the stock price of PT Hanjaya Mandala Sampoerna Tbk, both individually and simultaneously, over the 2013–2024 period. The study employed a quantitative approach using secondary data obtained from the company's statements of financial position, income statements, and stock price records. The population comprised all financial statements of PT Hanjaya Mandala Sampoerna Tbk, while the sample consisted of financial statements published during the observation period. The results of the classical assumption tests indicate that the regression model satisfies the required analytical assumptions and is appropriate for examining the relationships among the variables. The findings reveal that Net Profit Margin (NPM) does not have a significant effect on stock prices, suggesting that the company's profitability is not the primary consideration for investors in making investment decisions. In contrast, Price-to-Book Value (PBV) has a positive and significant effect on stock prices, indicating that market valuation plays an important role in influencing stock price movements. Furthermore, Net Profit Margin (NPM) and Price-to-Book Value (PBV) jointly have a significant effect on stock prices, demonstrating that the combination of profitability and market valuation indicators provides meaningful insights into the stock price movements of PT Hanjaya Mandala Sampoerna Tbk.